(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: This study aimed to develop and validate a stability-indicating reverse-phase high-performance liquid chromatography (RP-HPLC) method for the quantitative analysis of empagliflozin in pharmaceutical formulations. Materials and Methods: The method was developed using an Agilent C18 column (5μm; 4.6 x 250 mm) and a mobile phase consisting of a mixture of methanol/ 0.05% pH 3.3 acetic acid (75:25) at a flow rate of 1 ml/min with UV detection at 224 nm. The developed RP-HPLC method demonstrated linearity with a correlation coefficient (r) of >0.999. Forced degradation studies revealed the method’s ability to separate and quantify empagliflozin from its degradation products. The actual percentage degradation ranged from 2.85% to 7.43%. Precision was established where the mean interday and intraday RSD were 0.36% and 0.17%, respectively. Result and Discussion: The method’s robustness was confirmed, which had negligible effects on the assay results (<0.2% RSD). The method was applied to commercially available tablets, yielding an average (SD) empagliflozin recovery of 100.44% (0.18). Conclusion: This RP-HPLC method is suitable for routine analysis of empagliflozin in pharmaceutical formulations and can be employed for stability studies and quality control purposes, ensuring the drug’s quality and efficacy throughout its shelf life.